Dayak Ngaju Customary Sanctions as a Rehabilitation Mechanism for Drug Addicts in Central Kalimantan - Anwar, Khairil; Saefulloh, Ahmad; Surawan, Surawan; Nalus, Syafrul; Zuzanti, Zakia (El-Mashlahah, 2025)
The high number of drug addicts who have been successfully rehabilitated in Central Kalimantan (2,982 people) in the last 7 years always relates to the role of Dayak tribal leaders. Drug abuse is a significant threat to social cohesion and the sustainability of Dayak culture. The research aimed to analyze how Dayak Ngaju customary sanctions are applied in the rehabilitation of drug addicts and their impact on preserving cultural values. The study was a qualitative approach and used in-depth interviews and participant observations to collect the data from traditional figures and Dayak communities. The findings showed that Customary Sanctions function not only as a form of punishment but also as an effective rehabilitation tool, fostering a sense of accountability and strong social bonds. The study’s implications underscore the importance of integrating local wisdom into drug abuse prevention efforts as a means to reinforce the community’s social and cultural networks. Future research is recommended to explore the long-term effectiveness of these sanctions in preventing relapse and to compare similar practices across Indigenous communities.